Application Of Neuromarketing Methods In Improving The Effectiveness Of Product Marketing Strategies: An Approach To The Cosmetics Industry - Harahap, Wirahma Dina; Nasution, Fadillah Salsabila (Marcha Institute, 2023)
This study investigates the application of neuromarketing methods in improving the effectiveness of product marketing strategies in the cosmetics industry. Using brain scanning technologies such as MRI or EEG, neurological data is collected to understand consumers' brain responses to cosmetic product advertisements. Findings suggest that neuromarketing can provide valuable insights into consumer preferences and behavior, but also highlight challenges related to ethics, privacy, and data interpretation. The practical implications of this study are the need for deeper integration of neuromarketing findings with conventional knowledge of consumer behavior, as well as the need for strict policies in data management and consumer privacy protection. Future research could deepen the understanding of brain responses to cosmetic products through longitudinal studies and explore the ethical and social implications of using neuromarketing technologies in the context of marketing cosmetic products.